(untitled) (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Free-throw is the only isolated and stable situation in basketball where psychological aspects can be isolated during the competition. The aim of the current study is to analyze the effectiveness of free-throws according to the number of teammates who supported (i.e., showed affection) the shooter before throwing. The study sample included 319 free-throws of men's and women's semi-finals and finals of the Spanish Under-16 and Under-14 Championship. The results showed significant differences when receiving affection in the free-throws after a foul. The significant variables are the shooter’s free-throws percentage during the game and in the first free-throw. This finding leads the author to suggest that coaches should dedicate enough time to practice the free-throw as an individual task in the training sessions, as well as encouraging teammates’ cohesion and affection when the shooter is performing a free-throw.